Rapid, sensitive separation of the three main isoflavones in soybean using immunoaffinity chromatography. Issue 6 (March 2016) - Qu, Huihua; Qu, Baoping; Wang, Xueqian; Zhang, Yue; Cheng, Jinjun; Zeng, Wenhao; Liu, Shuchen; Wang, Qingguo; Zhao, Yan
Abstract : Daidzin, genistin, and glycitein are major isoflavone compounds in soybean that are indispensable nutrients in traditional Chinese foods. Generally, strategies for detecting and separating soy isoflavones have been based on HPLC and chromatographic techniques, which are tedious and time‐consuming procedures. In the present study, we developed an ELISA‐based approach for daidzin detection using a broad‐specificity monoclonal antibody (clone number: AA9) with an effective detection range of 10–10 000 ng/mL. Subsequently, we prepared an immunoaffinity column by coupling the monoclonal antibody AA9 to CNBr‐activated Sepharose 4B. Our results demonstrate that the immunoaffinity column can efficiently and specifically extract daidzin, glycitein, and genistin from numerous structurally similar soy isoflavones in leguminous plants, thereby providing a new method for the extraction of target components from similar compounds in natural products.